Work Conditions of the Mortuary Attendant in Ghana: A Qualitative Study - Anita Fafa Dartey PhD, M Nursing, OHNP, RN (SAGE Publishing, 2021)
Mortuary workers play a crucial role in healthcare delivery by providing after-life care for dead bodies. Mortuary attendants ensure that corpses are well preserved before handing them over to bereaved families for burial. However, the work of mortuary attendants is a neglected area in most low- and middle-income countries, Ghana inclusive.This study explored the nature, duties and job requirements of mortuary attendants in three regions of Ghana. A descriptive exploratory study that utilised a qualitative approach was conducted. Nineteen mortuary attendants who worked in nine mortuary facilities in three regions were purposively selected and interviewed for the study. Semi-structured interviews were audio-recorded using an interview guide. Verbatim transcription of conversations was done, data were manually coded and analysed thematically. Scientific trustworthiness was ensured through applications of the philosophies of credibility, dependability, confirmability and transferability. Three themes were identified: nature of the work of mortuary attendants; qualification and training requirements; and working conditions of mortuary attendants. The emerged sub-themes revealed the critical role played by attendants in preserving the bodies for the families; the majority of attendants got their skills through apprenticeship and challenging work conditions. The lack of structured formal education among mortuary attendants exposes them to occupational hazards and leads to poor service delivery. It is recommended that a formal programme for training, certification and recruitment of mortuary attendants be instituted to equip them with the needed knowledge and skill to enable them to meet the demands of their work.